Croatia after the assassinations: Chances for new reform dynamics - Tomislav Maršić (Stiftung Wissenschaft und Politik (SWP), 2008)
Croatia is under shock: Two commissioned murders, with obvious political links to the Mafia, have been carried out in quick succession on the streets of the country. Today, some eight years after the beginning of the 'second transformation' during which the country shifted from a semi-autocratic presidential system to parliamentary democracy, and shortly before the conclusion of negotiations on Croatia's accession to the EU, nobody would have reckoned with this kind of Mafia-style score-settling. The resulting wave of indignation will force the Croatian government, after years of passivity, to take the offensive and to adopt substantial reforms. This task requires nothing less than the political neutralization of influential figures. These individuals, who established excellent links to the political class during the war, are still present in some 'coordinating points of power.' Yet, part of this pressure for reform comes from the outside too: Shortly before the publication of the EU Commission's progress report, the government had to demonstrate its good faith. It removed the Interior and Justice Ministers, in order to allay French, German and Dutch reservations regarding Croatia's accession to the EU
Keywords: 320